The Social Production of Financial Inclusion of Generation Z in Digital Banking Ecosystems - Diana Kangwa; Joseph Thokozani Mwale; Junaid M. Shaikh (Australasian Accounting, Business and Finance Journal, 2021)
Digital finance is an emerging frontier of financial sector development in the contemporary 21st century. In spite of the known benefits of digital finance, there is a widely held view that digital financial services have not adequately permeated vast segments of society given the disparities in the availability of finance, its accessibility, and use. Therefore, the evolution of financial technologies along with digital consumer behaviourism in the present age presents scope for re-modelling conventional financial business models to particularly enhance the financial inclusion of Generation Z. This generation presumably has a unique mental construct of digital financial inclusion on account of its financial needs and circumstances, and its intrinsic digital consumer behaviourism. Therefore, this article espouses the Lefebvrean Social Production of Space as a novel theoretical lens through which financial inclusion of Generation Z could be better conceptualised to provide predictive insight for the future development of inclusive digital banking ecosystems. To this end, the article demonstrates, under the Zambian context in sub-Saharan Africa, that Generation Z has the propensity and competence to use digital technologies, but its adoptive response to digital finance is shaped by the perception that conventional banking and finance is highly exclusive. This suggests that the conventional banking ecosystem operates along a continuum between social equity and financial sustainability, posing a conceptual challenge of designing financial business models that are equitable without undermining the sustainability of the ecosystem. It is hereby recommended that for a digital banking ecosystem to be authentically inclusive of Generation Z there must be participatory accountability that considers and embraces the generation’s bidding strategies for financial inclusion, and further facilitates empowerment of this clientele based on the co-evolutionary dynamics of financial technology and digital consumer behaviourism.
Keywords: Financial inclusion; Generation Z; Social production of space; Digital banking ecosystem